Anesthesia Approach for Nephrectomy in Full-Term Neonate with Suspected Wilms Tumor and Patent Foramen Ovale: A Case Report - Katarina, Ida; Otniel Adrians Labobar; I Putu Kurniyanta (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Nephrectomy for Wilms tumor presents a considerable challenge in pediatric anesthesia. This study aimed to describe the anesthesia approach for nephrectomy in a full-term neonate with suspected Wilms tumor and patent foramen ovale. Case presentation: A 25-day-old male neonate was referred with a longstanding intraabdominal mass present since birth. Echocardiography revealed a patent foramen ovale with a diameter of 2.7 mm and a left-to-right shunt. The patient also had a diagnosis of partial ileus obstruction, likely caused by the tumor's pressure on the left kidney. Preoperative fasting adhered to a "6-4-3-1" regimen. Normoglycemia was maintained throughout the perioperative period. The case was managed under general anesthesia without the use of the rapid sequence induction technique. Caudal analgesia was administered using 1.14 ml of 0.175% bupivacaine. Vigilant monitoring of blood loss, prevention of hypothermia, and effective pain management are vital aspects of the surgical procedure. For postoperative pain management, analgesia and morphine infusion were employed. The patient was then transferred to the neonatal intensive care unit (NICU) for observation for any signs of complications related to anesthesia and surgery. Conclusion: Nephrectomy in neonates is one of the challenges of pediatric anesthesia. Pre-anesthesia preparation in relation to hypertension control, analgesia plan and postoperative care site, transfusion strategy, and management of intravascular extension.